Spatial Pattern of Rural Socioeconomic Condition in Ayer Lanas, Jeli,Kelantan. - Leong, Marieanne Christie (2013)
This study explores the present socioeconomic situation in rural Kelantan village in spatial context by integrating socioeconomic data with remotely-sensed data in Geographic Information System (GIS). Socioeconomic data were collected through household interview survey from spatially randomly selected households and linked to GIS using household's respective geographical position system (GPS) coordinate to produce various thematic maps on selected socioeconomic attributes. Remotely-sensed data used in the study is satellite imagery obtained from Bing map and is used as a base map for the incorporation of socioeconomic data with its respective GPS coordinate. Land cover was assessed to produce a general land use map of Ayer Lanas with an aim to provide a better picture of the local environment. The result of the study found that the residents in Ayer Lanas have a fairly modern way of living despite coming from a low-income family. Most of the respondents agreed that development in Ayer Lanas had changed their lifestyle and brought about good impacts to the neighbourhood except for job opportunities which they are in dire need of. In addition, several facilities have been identified as critically needed to accommodate increasing development in the area. This study also illustrated statistical data in spatial context to generate location-based information compared to conventional method which only utilises statistical data.